Lysophosphatidic acid receptors LPA(4) and LPA(6) differentially promote lymphocyte transmigration across high endothelial venules in lymph nodes - Hata E; Sasaki N; Takeda A; Tohya K; Umemoto E; Akahoshi N; Ishii S; Bando K; Abe T; Kano K; Aoki J; Hayasaka H; et al. (OXFORD UNIV PRESS, 2025)
Naive lymphocytes continuously migrate from the blood into lymph nodes (LNs) via high endothelial venules (HEVs). To extravasate from the HEVs, lymphocytes undergo multiple adhesion steps, including tethering, rolling, firm adhesion and transmigration. We previously showed that autotaxin (ATX), an enzyme that generates lysophosphatidic acid (LPA), is highly expressed in HEVs, and that the ATX/LPA axis plays an important role in the lymphocyte transmigration across HEVs. However, the detailed mechanism underlying this axis's involvement in lymphocyte transmigration has remained ill-defined. Here, we show that two LPA receptors, LPA(4) and LPA(6), are selectively expressed on HEV endothelial cells (ECs) and that LPA(4) plays a major role in the lymphocyte transmigration across HEVs in mice. In the absence of LPA(4) expression, lymphocytes accumulated heavily within the HEV EC layer, compared to wild-type (WT) mice. This accumulation was also observed in the absence of LPA(6) expression, but it was less pronounced. Adoptive transfer experiments using WT lymphocytes revealed that the LPA(4) deficiency in ECs specifically compromised the lymphocyte transmigration process, whereas the effect of LPA(6) deficiency was not significant. These results indicate that the signals evoked in HEV ECs via the LPA(4) and LPA(6) differentially regulate lymphocyte extravasation from HEVs in the peripheral LNs.